POLY (L-LACTIDE) DEGRADATION BY SOME ACTINOMYCE ISTRAINS ISOLATED FROM VIETNAM - Huy, Nguyễn Quang; Dương, Đỗ Huy; Chiều, Lê Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY Degradable polymers are increasingly considered as an attractive alternative to the current petroleum-derived plastics from the viewpoint of environmental protection and solid-waste management. Various types of biodegradable polyesters are presently manufactured, such as poly (L- lactide) (PLA), poly (b-hydroxybutyrate) (PHB), poly (e-caprolactone) (PLC) and poly (butylenes succinate) (PBS)... We used the plate count and clear zone methods to evaluate the distribution of polyester-degrading microorganism in different soil environments and found some actinomyces were degraded PLA. Two of them, strains XKG3 and XKG5 were created large clear zone on agar plate containing PLA as carbon sources. Base on morphology and some of biochemistry characterizations two actinomyces trains isolated XKG3 and XKG5 were belong to Streptomyces groups. Strains XKG3 and XKG5 after 20 days cultivation were degraded from 41.04% to 53.42% total PLA (base on molecular weight) added in the media culture and 51.75% to 65.91%, respectively total amounts of PHB. Two strains could grew well in the media have only PLA film as carbon and energy sources. Two actinomyces have ability produce some enzymes degradable such as amylase, protease, cellulase. Further studies with the selected microorganisms will help us to better understand their actual potential to biodegradation of biopolymer.